THE PETROGENESIS AND TECTONIC SETTING OF ULTRAMAFIC ROCKS FROM ITI AND KALLIDROMON MOUNTAINS, CONTINENTAL CENTAL GREECE: VESTIGES OF THE PINDOS OCEAN - Karipi S.; Tsikouras B.; Hatzipanagiotou K. (My University, 2006)
The Iti and Kallidromon ophiolites, in continental central Greece, consist mainly of an ophiolite melange overthrust by variably serpentinized ultramafic rocks. They include lherzolite and harzburgite; dunite pods occur within the lherzolite at Kallidromon. All rock types display typical textures of Alpine-type mantle rocks. Spinet, olivine and pyroxene compositions are similar to analogous phases from oceanic peridotites. The lherzolite contains an aluminous spinet. The dunite and harzburgite contain two compositional variants of Cr-rich spinet, both commonly present in zoned grains, one with higher Cr# and a second with lower Cr#. Linear variations of Al2O3, CaO, V and Ni with MgO, coupled with incompatible and rare-earth-element depletion and mineral compositions, suggest prior events of partial melting in both the lherzolite and harzburgite. The LREE enrichment in the harzburgite, as well as the development of Cr-rich spinet and tremolite and the PGE distribution in both the dunite and harzburgite, are consistent with a history of melt-peridotite interaction. The melt is considered to have been of boninitic composition, generated in the mantle wedge above a subduction zone. The harzburgite was formed at values of smaller melt:rock ratio relative to the dunite owing to partial assimilation of clinopyroxene and orthopyroxene from the host lherzolite. The dunite is considered to have been formed by assimilation of clinopyroxene and orthopyroxene, and replacement of Al-rich spinet by Cr-rich spinet, when locally ponded boninitic melts reacted with the host lherzolite. In both the harzburgite and dunite,